2014
DOI: 10.1158/1078-0432.ccr-13-2613
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Sensitizes EGFR-TKI–Resistant Human Lung Cancer Cells In Vitro and In Vivo through Inhibition of IL-6 Signaling and EMT Reversal

Abstract: Purpose: The EGF receptor tyrosine kinase inhibitors (EGFR-TKI) have become a standard therapy in patients with EGFR-activating mutations. Unfortunately, acquired resistance eventually limits the clinical effects and application of EGFR-TKIs. Studies have shown that suppression of epithelial-mesenchymal transition (EMT) and the interleukin (IL)-6/STAT3 pathway may abrogate this acquired mechanism of drug resistance of TKIs. This study aims to investigate the effect of metformin on sensitizing EGFR-TKI-resistan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
186
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(201 citation statements)
references
References 47 publications
12
186
2
1
Order By: Relevance
“…42) Inhibiting IL-6/STAT3 pathway suppressed cancer cell proliferation and restored the sensitivity to TKI. 26,43) This suggests that the antagonism of IL-6/STAT3 pathway could be therapeutically beneficial for the treatment of drug-resistant tumors that are driven by EMT-like phenomena. 44) In this study, we observed the activation of IL-6/STAT3 signaling pathway in ER cells, elevated IL-6 promotes EMT through altered expression of N-cadherin, vimentin and E-cadherin leading to enhanced cancer invasion.…”
Section: Discussionmentioning
confidence: 99%
“…42) Inhibiting IL-6/STAT3 pathway suppressed cancer cell proliferation and restored the sensitivity to TKI. 26,43) This suggests that the antagonism of IL-6/STAT3 pathway could be therapeutically beneficial for the treatment of drug-resistant tumors that are driven by EMT-like phenomena. 44) In this study, we observed the activation of IL-6/STAT3 signaling pathway in ER cells, elevated IL-6 promotes EMT through altered expression of N-cadherin, vimentin and E-cadherin leading to enhanced cancer invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its roles in cancer invasion, metastasis and chemoresistance, the inhibition or reversion of the EMT has been regarded as a promising strategy for treating cancer. Several agents, including a mechanistic target of rapamycin inhibitor (6) and metformin (7), have been reported to suppress EMT in lung cancer. However, effective approaches for inhibiting the EMT have not been established.…”
Section: Introductionmentioning
confidence: 99%
“…To the Editor: The Protocolised Management in Sepsis (ProMISe) trial (April 2 issue) 1 completes a trio of studies [1][2][3] that question the further application of early, goal-directed therapy (EGDT) as suggested by Rivers et al 4 In particular, these trials consistently show no survival benefit with regard to the mandated use of central venous oxygen saturation (ScvO 2 ) monitoring. However, it remains questionable whether the results of the three trials support this claim.…”
Section: Early Goal-directed Resuscitation For Septic Shockmentioning
confidence: 99%
“…These results strongly support the pivotal role of the SSC guidelines that include EGDT. [1][2][3] Although these trials reveal that monitoring of central venous pressure is not mandatory, they show no harm in EGDT and certainly do not suggest that other aspects of the guidelines be called into question. We are concerned that the conclusions promulgated by the triad of trials will be misinterpreted and will cast doubt on the importance of SSC protocols for sepsis detection and treatment.…”
Section: Doi: 101056/nejmc1506514mentioning
confidence: 99%
See 1 more Smart Citation